PENGARUH DEFATTING DAN SUHU EKSTRAKSI TERHADAP KARAKTERISTIK FISIK GELATIN TULANG IKAN GABUS - Wulandari Wulandari; Agus Supriadi; Budi Purwanto (Jurnal FishtecH, 2013)
The purpose of this research was to observe the effect of defatting and extraction temperature on the physical properties of snakehead fish bone gelatin. The Factorial Randomized Block Design was used with two factors of treatment and 2 replications. The different pretreatment (defatting and non-defatting) and three different extraction temperature (60, 70 and 80 0C). The parameters were yield, viscosity, gel strength and melting point. The best treatment was defatting with extraction temperature 70 oC had gel strength 202,9 bloom, viscosity 3,87 cP, melting point 22,5 oC and yield 3,53%.